An Exploration into the Service Provision and Availability of Thrombolysis Treatment for Hyper-Acute Stroke in the NHS: A Critical Review - Beale, Emma (2011)
Background Stroke is a major cause of death and adult disability in the United Kingdom. However, despite the large proportion of victims from Stroke, advances in treatment and service provision for hyper acute stroke had remained underdeveloped in comparison to other areas of the NHS. Within the last decade advances have been made in improving holistic stroke care as well as an increase in focus on the service provision for hyper acute stroke.